TOWARDS A PHENOMENOLOGICALLY GROUNDED UNDERSTANDING OF SOCIAL THEORY. II. THE PROBLEM OF SUBJECTIVITY - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2015)
The second part of the article aims to specify the paradox of subjectivity and to explicate the phenomenological foundations of the methodology of the social sciences. There are four main problems. They are following: first, the problem of the relation between sociology and philosophy; second, the problem of the relation between “I” and “It”; third, the problem of the relation between ideal types and practical typification; fourth, the problem of the relation between phenomenological epoché and epoché of the natural attitude.